The Time Course of Quadriceps Strength Recovery After Total Knee Arthroplasty Is Influenced by Body Mass Index, Sex, and Age of Patients: Systematic Review and Meta-Analysis - Paravlic, Armin H.; Meulenberg, Cécil J.; Drole, Kristina (Frontiers in Medicine, 2022)
Introduction: For osteoarthritis patients who have undergone total knee arthroplasty (TKA), quadriceps strength is a major determinant of general physical function regardless of the parameters adopted for the functional assessment. Understanding a time course of quadriceps strength recovery and effectiveness of different rehabilitation protocols is a must. Therefore, the aim of the present study was to: (i) determine the magnitude of the maximal voluntary strength (MVS) loss and the time course of recovery of the quadriceps muscle following TKA; (ii) identify potential moderators of strength outcomes; (iii) investigate whether the different rehabilitation practices can moderate the strength outcomes following TKA, respectively. Design: General scientific databases and relevant journals in the field of Orthopaedics were searched, identifying prospective studies that investigated quadriceps’ MVS pre-to-post surgery. Results: Seventeen studies with a total of 832 patients (39% males) were included. Results showed that in the early postoperative days, the involved quadriceps’ MVS markedly declined, after which it slowly recovered over time in a linear fashion. Thus, the greatest decline of the MVS was observed at three days after TKA. When compared to pre-operative values the MVS was still significantly lower three months after the TKA and did not fully recover up to six months following the TKA. Further, a meta-regression analysis identified that the variables: time point of evaluation, patient age, sex, and BMI, significantly moderate the MVS of the quadriceps muscle. Conclusions: The analysed literature data showed that the decrease in strength of the involved quadriceps muscles following TKA is considerable, and lasts for several months post-surgery. Therefore, we recommend to specifically target the strengthening of the knee extensor muscles, preserve the motor control, and apply appropriate nutrition to ensure a holistic quadriceps muscle recovery. Since age, sex and BMI were found to be moderating factors in patient’s recovery, further research should include specific analyses considering those moderators.